Anglophone culture through the Western Balkan lens: a corpus-based study on the strategies used for rendering extralinguistic elements of culture in Montenegrin subtitling - Božović, Petar (Círculo de Lingüística Aplicada a la Comunicación, 2021)
One of the most demanding aspects of intercultural communication is rendering the elements of foreign culture from source to target linguocultural system. As today more people are exposed to audiovisual than any other form of text, cultural representation is an important issue as these texts can be a powerful tool for construction or deconstruction of cultural and sociological stereotypes, dissemination of ideas, facilitating intercultural communication, etc. Hence, this study attempts to shed light on how the Anglophone culture is rendered in subtitling and what could be some underlying reasons for that. To this end, we have constructed a morphosyntactically annotated parallel English – Montenegrin corpus of TV subtitles consisting of 110 episodes of three different TV series that were broadcast on the public service broadcaster of Montenegro and scrutinized it to map the strategies used for rendering extralinguistic elements relying on the analytical framework proposed by Pedersen (2011).